An analysis of the comedy-style compositions of northern language songs by Witoon Jaiprom - Sermthong, Aekthida (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2025)
The objective of this research article is to study the biography and works of comedian Kham Muang, Witoon Jaiprom. Study the methods of composing songs and the concept of Kham Muang comedy. Study the content and strategies for telling stories in the Kham Muang comedy songs. Including studying the literary value of the Kham Muang comedy songs which Witoon Jaiprom is the author and the singer himself. There are a total of 15 songs. Research and data collection methods were used by In-dept Interview, documentary research and textual analysis. The results of the research found that passion for singing, personal characteristics, experiences, and opportunities have driven Witoon to succeed, to become a singer and the composer of the unique Khammuang comedy song. In addition, music composition is divided into 2 eras: 1st era There was a style of song writing that had alternating singing and speaking parts, called sectional music composition. The second era called humorous content song composition which is funny song content. Song writing pattern or musical forms that are commonly used is Strophic Form, which is a style of singing that has the same melody throughout but the lyrics are changed to AAA format. The funny concept that is most used in music composition is Relief theory or relaxation theory. In the manner of creating laughter, humor, and reducing mental tension by raising social issues in the song content. Most of them bring out the comedy from the storyline which is clearly communicated and straightforward, consisting of 3 characteristics: a storyline about behavior, the storyline revolves around social issues, and storylines about culture. In addition, each song also has all 7 elements of storytelling, including linear storytelling. In terms of the literary value of the song, it was found that consist of the use of images, using literary questions, word play, and sound play. There is also the use of interjections. and the use of fluctuating words in songs as well.